Traditional games as warm-up activities in elementary physical education: A qualitative study of teachers’ perspectives - Gunawan, Gugun; Hambali, Sumbara; Sobarna, Akhmad; Shafie, Mohd. Shariman (EduStream: Jurnal Pendidikan Dasar, 2026)
Warm-up activities in elementary physical education are often treated as routine preliminaries, even though they can shape students’ readiness, engagement, and early learning experience. Traditional games may offer a more enjoyable and culturally responsive alternative to conventional warm-up routines. This study explored elementary physical education teachers’ perspectives on the use of traditional games as warm-up activities. The study employed a qualitative descriptive design involving six elementary physical education teachers from public and private schools in Cimahi City, West Java, Indonesia. Data were collected from 26 to 30 April 2025 through non-participant lesson observations, semi-structured interviews, and document analysis. The data were analyzed thematically. Four interrelated themes were identified. First, teachers positioned traditional games as a structured part of the opening phase of the lesson rather than as incidental play. Second, teachers perceived traditional games as beneficial for both physical readiness and affective engagement because students appeared more enthusiastic, active, and willing to participate. Third, teachers attached pedagogical, social, and cultural value to traditional games because they were seen as supporting cooperation, discipline, sportsmanship, and cultural appreciation. Fourth, implementation was shaped by contextual constraints, including limited facilities, restricted lesson time, shared activity spaces, and students’ declining familiarity with traditional play. Across themes, teacher adaptability emerged as central to the successful use of game-based warm-ups. The findings suggest that traditional games can function as low-cost, culturally responsive, and educationally meaningful warm-up resources in elementary physical education.